Perencanaan Pengembangan Industri Asbes Dengan Metode Analytical Hierarchy Process dan Linear Goal Programming - Muhammad Baderru Syarif (Yayasan Azzuhri Lengkok Lombok Timur, 2023)
CV Lestari is a company that produces asbestos. There are several asbestos production centers in the city of Jakarta, one of which is CV. CV Lestari is located in Buaran, East Jakarta. In implementing this plan, CV Lestari must compete with the companies or factories that follow it. CV Lestari must retain customers and anticipate ever-increasing market needs. Knowing these conditions, the author will provide alternatives to overcome these problems by identifying and analyzing company conditions, not only internal and external conditions but also profits, company competition using the Analytical Hierarchy Process (AHP) and Linear Goal Programming (LGP) methods. In this final project, the Analytical Hierarchy Process (AHP) method is used because by using this method the priority calculation results show the roof tiles that consumers want compared to other products. CV Lestari, which produces asbestos, will try to improve product quality. their product. The Linear Goal Programming (LGP) method is also used using the QS (Quantitative System) program to obtain a planning strategy for the development of the roof tile industry based on sequential priorities, then the analysis is emphasized in calculating the quantity of roof tile products to find better ones. So, the goals achieved with optimal valves are also anticipating market needs and maximizing company/factory profits as well. Keywords: AHP, LGP, planning developing